2015
DOI: 10.5492/wjccm.v4.i3.258
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of critically ill cancer patients with Acinetobacter baumannii infection

Abstract: The mortality rate in critically ill patients with both HM, and AB infections who are admitted to the ICU is high. The variable most associated with increased mortality was a BLL ≥ 2.6 mmol/L in the first day of stay in the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…Between different types of cancer, hematological malignancies seem to have a worse prognosis as very recently demonstrated by Torres et al 21 We observed a higher occurrence of infection with methicillin-resistant Staphylococcus aureus, A baumannii, and microorganisms resistant to carbapenems in NS than in S. Namendys-Silva et al have also recently demonstrated a high mortality in critically ill patients infected by A baumannii. 22 Acinetobacter baumannii and gram-negative bacteria resistant to carbapenems are almost never eradicated with a single class of antibiotics, but a polypharmacological strategy with the combination of different classes of antibiotics is required. This strategy is infrequently applied during the initial empirical antibiotic treatment, and this could justify the high mortality in patients infected with A baumannii and carbapemenresistant bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Between different types of cancer, hematological malignancies seem to have a worse prognosis as very recently demonstrated by Torres et al 21 We observed a higher occurrence of infection with methicillin-resistant Staphylococcus aureus, A baumannii, and microorganisms resistant to carbapenems in NS than in S. Namendys-Silva et al have also recently demonstrated a high mortality in critically ill patients infected by A baumannii. 22 Acinetobacter baumannii and gram-negative bacteria resistant to carbapenems are almost never eradicated with a single class of antibiotics, but a polypharmacological strategy with the combination of different classes of antibiotics is required. This strategy is infrequently applied during the initial empirical antibiotic treatment, and this could justify the high mortality in patients infected with A baumannii and carbapemenresistant bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the incidence of ICU-acquired A. baumannii infections (8.4%) was lower than that reported in India (10%) 14 and higher than that observed in Mexican patients with cancer (4.6%). 15 This variability in incidence rates could be explained by differences in the reinforcement and compliance of infection control measures, especially hand hygiene practices and the decontamination of hospital environment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that crude mortality rates in patients with AB bacteremia varied between 30 and 76%, and factors associated with worse prognosis include immunosuppression (Gulen et al, 2015 ; Townsend et al, 2015 ; Gu et al, 2016 ), drug resistance (Lee et al, 2007 ; Sunenshine et al, 2007 ; Fu et al, 2015 ; Guo et al, 2016 ), severity of underlying illness (Seifert et al, 1995 ; Chopra et al, 2013 , 2014 ; Nutman et al, 2014 ), inappropriate antimicrobial therapy (Esterly et al, 2011 ; Huang et al, 2012 ; Shorr et al, 2014 ; Freire et al, 2016 ), septicemia (Huang et al, 2012 ; Ñamendys-Silva et al, 2015 ; Freire et al, 2016 ), and prior antibiotic exposure (Chopra et al, 2013 , 2014 ; Gu et al, 2016 ; Liu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%